The G20210A Prothrombin Polymorphism Is not Associated with Increased Thromboembolic Risk in a Large Protein C Deficient Kindred - Bovill, Edwin G.; Hasstedt, Sandra J.; Callas, Peter W.; Valliere, Julia E.; Scott, Bruce T.; Bauer, Kenneth A.; Long, George L. (Thrombosis and Haemostasis, 2000)
Likelihood analysis was used to test the effect of the G20210A prothrombin mutation and the His107Pro protein C mutation (resulting from a C insertion) on thrombosis status and prothrombin level in a large kindred of French Canadian descent with type I protein C deficiency. Genotypes were available on 279 pedigree members or their spouses. Of this total, 36 pedigree members were heterozygous for the G20210A variant and one pedigree member was homozygous for G20210A, while 64 were heterozygous for the His107Pro protein C mutation. The factor V Leiden mutation (Arg506Gln) was observed in only one of 181 tested family members. Objectively verified thrombosis was present in 26 of the 279 pedigree members. Thrombosis was suspected in an additional 19 pedigree members. The transmission disequilibrium test of Spielman, 1996, as extended to pedigrees, was used to test for excess transmission of G20210A or His107Pro to thrombosis cases, with transmission of 0.5 specifying no effect. Although the His107Pro mutation was over transmitted (0.837 ± 0.075 p <0.001) to thrombosis cases in this pedigree, the G20210A variant was not (0.491 ± 0.130 NS).Measured genotype analysis was used to examine a total of 184 individuals for the relationship between prothrombin level and both the G20210A variant and thrombosis. The G20210A variant increased prothrombin level from 97 ± 2% to 124 ± 4% (p <0.0001), but thrombosis status was not associated with any additional increase in prothrombin level. Thus, in a large thrombophilic, protein C deficient kindred, with the G20210A variant present in a proportion (13%) far higher than the general Caucasian population (∼2%), neither the presence of the variant nor the plasma concentration of prothrombin were associated with increased risk for thrombosis. These findings contrast with those of others who have established the G20210A variant as a thrombophilic risk factor; and emphasize the complex nature of the multigenic pathogenesis of thrombophilia.
Keywords: Thrombophilia; protein C deficiency; G20210A prothrombin variant; thrombosis; hereditary